Utilization of Scientific Articles to Improve Learning Quality in Research Methods Courses - Rizky Febriani Pohan; Muhammad Rahman Rambe (Journal of Digital Learning and Education, 2023)
The purpose of this study was to determine the increase in learning outcomes of Research Methods students at the Faculty of Engineering, Civil Engineering Study Program, Graha Nusantara University Padangsidimpuan through the application of scientific article learning and to find out the perceptions and involvement of students in learning scientific articles used, especially the Research Result Report material. This research is important to do to improve the learning quality of the Research Methods course so that students can easily learn it. The research method is an experimental method with a one-group pretest-posttest research design because not all experimental characteristics and conditions can be regulated and controlled strictly as in other experimental research. Research instruments in the form of tests and questionnaires. Learning outcomes data were analyzed with the Wilcoxon and N-Gain tests. While the perceptions and involvement of students were analyzed with a Likert scale. The results showed that scientific articles increased student learning outcomes when learning Research Methods by 33.58%. Perception and involvement of students in learning with scientific articles obtained positive results. This can be seen from the average student scores in the perception and student involvement questionnaire, both of which are in the medium category. The results of this study show the effectiveness of learning scientific articles in the Research Methods course which shows that the level of success achieved from learning scientific articles is in accordance with the planned learning objectives